MATHEMATICS CILOK WITH CARROT CONTENT AS A HEALTHY AND EDUCATIONAL STREET FOOD INNOVATION - Erviana Vilka Natania; Silfi Septiyani; Kayla Litadewi Adiastrie; Muhamad Bahrul Irfan; Muhamad Dhiqi Musyafa (Ravine Publisher, 2023)
Cilok is a popular street food because it is practical, satiate, and cheap. Behind that, nutrition's cilok has low value, and street food has a negative stigma. Then, the Indonesian population does not consume enough fruit and vegetables. Therefore, adding vegetables, shape modifications, and hygienic packaging to cilok products is necessary so that people do not have to worry about consuming their favorite street food, creating a relatively high market opportunity. Based on this, Cilok Mathematics is here as a unique, healthy, and educational street-food innovation. The production process is divided into three stages: making, preparing peanut sauce, and packaging. It is hoped that the Cilok Mathematics product can expand the market while maintaining quality so that, in the future, this product has the potential to operate stably and consistently. Cilok Mathematics will register product patents, trademarks, and halal certificates in the next plan. Apart from that, in the production process, a production house will be promoted at the bazaar or other events, and each team will carry out promotions in their area so that Cilok Mathematics can become more widely known.